Response of sunflower-weed ecosystem to herbicide oxadiagryl and integrated weed management options: RESPONSE OF SUNFLOWER-WEED ECOSYSTEM TO HERBICIDE OXADIAGRYL AND IWM OPTIONS - ANITA MAHAPATRA; LOPAMUDRA MOHANTY; KULASEKARAN RAMESH; RAJKUMARI BHOL (Journal of Oilseeds Research, 2024)
Field experiment was conducted during summer, 2021 at Odisha University of Agriculture & Technology, Bhubaneswar to study the response of sunflower as a part of Integrated weed management with suboptimal, optimal and super optimal doses of oxadiargyl as pre-emergence spray with or without quizalofop ethyl 5 EC @ 37.5 g/ha at 15 - 20 DAS in sunflower hybrid "KBSH-44" revealed that weed free control has recorded the highest seed yield (2064 kg/ha), which remained at par with oxadiargyl @ 125 g/ha as pre-emergence spray fb one HW at 30 DAS with a seed yield of 1962 kg/ha with a WCE of 92.6% at harvest.